Paroxysmal Ocular Downward Deviation - J Gordon Millichap (Pediatric Neurology Briefs)
Paroxysmal ocular downward deviation in 13 children with spastic quadriplegia, mental retardation and cortical visual impairment is reported from the Department of Pediatric Neurology, Seirei-Mikatabara General Hospital, Hamamatsu, Shizuoka, Japan.